PENGAPLIKASIAN NILAI BUDAYA BERBASIS RELIGIUS PADA SASTRA DAERAH GUNA PENGENALAN PENDIDIKAN SEKSUAL PADA ANAK DAN REMAJA - Muhammad Asyura (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
The rise of cases of child sexual abuse requires solutions from an educational point of view. Value education according to Indonesian culture and religion also needs to be directed at aspects of sexuality although it is still considered taboo that can be applied to local literary texts. This study aims to describe the existence of sexual education in two legends of different cultures, namely the origin of Pontianak (Malay) and Mount Tangkuban Parahu (Sundanese) using a literary sociology approach. The description is then associated with religious-based cultural values (Islamic views) to be packaged neatly so that it can be conveyed by language teachers through literature. The results of this study show the existence of sexual education about forbidden marriage, acceptance of nature, and the process of self-maturation which is then linked to Islamic-based sexual education.